Implementation Organizational Agility Maturity Model at Tribe EWZ, PT. Telekomunikasi Indonesia TBK - Fitriah, Naila Mira; Tricahyono, Dodie (Jurnal Ekonomi, 2025)
This study uses a qualitative method, with data collection techniques carried out through data source triangulation, namely by obtaining data from various sources using the same method. The data collection tool used in this study is in-depth interviews conducted with six (6) informants, consisting of one (1) Tribe Leader, one (1) Squad Leader, one (1) Product Manager, one (1) Junior Product Manager, and two (2) Scrum Masters. The results of this study provide an overall picture of the maturity level of Tribe EWZ. In its implementation, the EWZ Tribe measurement uses the Wendler model which consists of 3 (three) Dimensions and 6 (six) Sub-dimensions, namely: Agility Prerequisites include: Agile Values, Technology; People Agility includes: Workforce, Change Management; Structure Enhancing Agility includes: Collaboration and Coordination, Flexible Structure. Based on these implementations, it is known that Tribe EWZ is at maturity stage 2: Agility Transition, which at this stage means that Tribe EWZ has implemented all three dimensions throughout most of the organization. However, Tribe's current position is considered insufficient by some parties, they hope that Tribe EWZ can reach the highest level which is 3: Organizational Agility.